Widely tunable surface plasmon resonance and uniquely superior SERS performance of Au nanotube network films. (30th April 2021) - Lin, Yongxing; Wang, Liang; Zhang, Haibao; Wu, Linfeng; Fan, Huibo; Liu, Xianglan; Zheng, Ruobing; Tian, Xingyou; He, Hui
Abstract: Three-dimensional Au network films with flexibility and transferability were fabricated based on sputtering deposition onto electrospun nanofibers as a template. The films are constructed using long Au nanotubes that are cross-linked with each other and that have dense nanoparticles on the tube wall surface. The surface plasmon resonance (SPR) peaks for the films are tunable in a wide range, from visible light to the near-infrared region, by tuning the inner diameter and/or wall thickness of the nanotubes. Such structured film exhibits significant surface-enhanced Raman scattering (SERS) activity with good signal uniformity and stability, and possesses great potential in the in situ detection of trace organic pollutants on a solid surface by simple transferring. This study provides a Au film with a unique structure and widely tunable SPR for in situ SERS sensing and other needs.